Effectiveness Analysis of BIOMOL and Light Trap Innovations Based on Environmental Impact Verification in the Wanua Wailan CSR Program in Pangolombian and Tondangow Subdistricts - Akmal Kholid Farhan; H.S.M Saragih; Dinatika Ummami; Panji Okta Triswianto; Brury Revlon Sarese (Journal of Political and Governance Studies, 2026)
Background The Wanua Wailan CSR program implemented by PT PLN Indonesia Power UP PLTP Lahendong in Pangolombian and Tondangow Subdistricts focuses on strengthening the circular economy through restorative agriculture and organic waste management. The main challenges include land degradation caused by the excessive use of chemical fertilizers and pesticides, as well as unmanaged organic waste. This study aims to analyze the effectiveness of BIOMOL and Light Trap innovations based on environmental impact verification in supporting the sustainability of the CSR program. Methods This research employs a mixed-methods approach, combining quantitative analysis through data on the reduction of chemical fertilizer and pesticide usage, as well as estimated GHG emission reductions with qualitative methods, including interviews, field observations, and program documentation. Results The results indicate that BIOMOL contributes to improving soil quality and reducing dependence on chemical inputs, while the Light Trap proves effective as an environmentally friendly pest control technology powered by renewable energy. Environmental impact verification shows a reduction in emissions of 100.4357 tons CO₂eq per year. Conclusion The integration of BIOMOL and Light Trap has been proven effective as a CSR innovation grounded in a socio-ecological economic approach. The findings underscore the importance of appropriate technology innovation and multi-stakeholder collaboration in enhancing the environmental sustainability impact of CSR programs.